History Teachers' Strategy in Integrating Historical Thinking Skills Through Academic Discussion Activities at SMA Negeri 1 Sangatta Utara - Fadilla, A. Nur; Rochmat, Saefur (Green Publisher Indonesia, 2024)
The changes that occur in history learning require critical thinking skill to support the teaching and learning process. The teacher needs to help students improve their historical thinking skill. This research aimed to a) find out and explain history teachers' understanding of historical thinking skill; b) explain the history teachers' strategy in integrating historical thinking skills through academic discussion activity; and c) know the factors that influence history teachers in integrating historical thinking skill through academic discussion activity. This research was qualitative research by using case study method. The research was conducted in SMA N 1 Sangatta Utara, with the research subjects were two history teachers and six students of XI class. Data collected by using observation, interview, and documentation techniques. Data analysis technique used Miles and Huberman model. The research result showed that a) the teachers understand historical thinking skill before conducting history learning by using academic discussion; b) the teachers' strategy in integrating historical thinking skill with academic discussipn was giving instruction gradually to students so that they can understand the use of historical thinking skill in history learning in academic discussion; and c) there are two factors that influence the teachers to integrate historical thinking skill and academic discussion namely a change in education system, and students condition which do not understand historical material and unable of students to develop critical thinking skills in history learning.